Genotype-phenotype correlation in neurofibromatosis type-1: NF1 whole gene deletions lead to high tumor-burden and increased tumor-growth. - Lennart Well; Kimberly Döbel; Lan Kluwe; Peter Bannas; Said Farschtschi; Gerhard Adam; Victor-Felix Mautner; Johannes Salamon (PLoS Genetics)
Neurofibromatosis type-1 (NF1) patients suffer from cutaneous and subcutaneous neurofibromas (CNF) and large plexiform neurofibromas (PNF). Whole gene deletions of the NF1 gene can cause a more severe phenotype compared to smaller intragenic changes. Two distinct groups of NF1 whole gene deletions are type-1 deletions and atypical deletions. Our aim was to assess volumes and averaged annual growth-rates of CNF and PNF in patients with NF1 whole gene deletions and to compare these with NF1 patients without large deletions of the NF1 gene. We retrospectively evaluated 140 whole-body MR examinations of 38 patients with NF1 whole gene deletions (type-1 group: n = 27/atypical group n = 11) and an age- and sex matched collective of 38 NF1-patients. Age-dependent subgroups were created (0-18 vs >18 years). Sixty-four patients received follow-up MRI examinations (NF1whole gene deletion n = 32/control group n = 32). Whole-body tumor-volumes were semi-automatically assessed (MedX, V3.42). Tumor volumes and averaged annual growth-rates were compared. Median tumor-burden was significantly higher in the type-1 group (418ml; IQR 77 - 950ml, p = 0.012) but not in the atypical group (356ml;IQR 140-1190ml, p = 0.099) when compared to the controls (49ml; IQR 11-691ml). Averaged annual growth rates were significantly higher in both the type-1 group (14%/year; IQR 45-36%/year, p = 0.004) and atypical group (11%/year; IQR 5-23%/year, p = 0.014) compared to the controls (4%/year; IQR1-8%/year). Averaged annual growth rates were significantly higher in pediatric patients with type-1 deletions (21%/year) compared with adult patients (8%/year, p = 0.014) and also compared with pediatric patients without large deletions of the NF1 gene (3.3%/year, p = 0.0015). NF1 whole gene deletions cause a more severe phenotype of NF1 with higher tumor burden and higher growth-rates compared to NF1 patients without large deletions of the NF1 gene. In particular, pediatric patients with type-1 deletions display a pronounced tumor growth.